Registration of declaration of factory and traffic in real estate legal owners of urban lands of the old city of Cerro Pasco, 2007-2011 - Blanco-Aliaga, Ovidio (2019)
The purpose of this work was to establish the association between the variables declaration of factory and real estate traffic legal in owners of urban properties of Cerro de Pasco. The work was correlational descriptive, with the stratified sample of 362 owners of properties in the city of Pasco. The instruments were the survey and questionnaire about traffic real state legal, design by the researcher. The results show that there is a significant correlation degree between the variables of study with a contingency coefficient, c= 0.71 and a chi square a= 0.05 and 5 Gl for a contingency table X2 calculated=262.00 greater than the value of X2 table= 11.070, rejecting the Ho, indicating that there is no relationship between the declaration of factory and real estate traffic legal. Also the declaration of factory nonregistered prevails with respect to the registered and the predominant real estate traffic legal is the offer devalued because the factory is not registered in the sample.